Modelo de diagnóstico energético com base em um sistema de avaliação de desempenho - Zanardo, Rafael Petri (2016)
Brazil has the largest tariffs cost of power in the world, with the aggravating circumstance of having the lowest development in energy efficiency. This context has undermined the competitiveness of Brazilian industrial sector, which consumes approximately one third of all power generated in the country. In the face of this scenario, the research developed in this dissertation aims to propose a model for diagnosing the level of energy performance in companies in the industrial sector, using both the concepts of organizational performance evaluation and approach to multicriteria decision aid. The modeling proposal was developed based on the assumptions of Key Performance Indicators (KPI), arranged in a hierarchical structure, where they were listed six fundamental points of view that if ramified in 58 critical success factors, selected from the recurrences identified in the theoretical framework. The determination of the influence of each indicator in the proposed analysis was performed by means of the judgment of priorities of the Hierarchical Analysis of Processes (AHP). To evaluate the interaction of performance indices of the indicators in modeling, developed spreadsheets through the software Excel® for data processing and report generation. The modeling was tested in a company located in the industrial pole of Manaus, returning in their evaluation phase of an index that represents the energy performance, allowing the discussion of results obtained. Subsequently, they were proposed actions of adequacy with the objective of simulating the potential performance gains achieved through the adoption of strategic actions. At the end, it is concluded that it is possible to diagnose the level of energy performance in companies in the industrial sector by means of tool proposal.